Physiological Elements In Job Satisfaction Of Special Education Teachers In Malaysia - et. al., Jumiah binti Mustapa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Previous studies have found that physiology is an important foundation in meeting a person’s satisfaction. This explains that, if the basics of physiology such as eating, drinking, living, appreciation and relationships can be met well, then one’s level of satisfaction is already beginning to be achieved. Similarly in the world of education, its citizens need a sense of satisfaction in working in order to motivate themselves to do better. Teachers are able to work contentedly once humanitarian values ​​are taken into account as valued, treated fairly, no additional burdens and given space to determine the action to be taken. Physiological needs need to be given attention by the school leadership so that teachers can achieve their job satisfaction. This study conducted will further detail the physiological elements in helping teachers, especially in special education to achieve their job satisfaction. This qualitative study involved 11 respondents consisting of coordinators of special education integration programs in each district in the state of Johor, Malaysia. Interviews were conducted and thematic analysis was conducted to obtain data interpretation. The findings of this study are expected to provide a clear picture of the physiological elements in job satisfaction of special education teachers.